Impact of pre-inoculating soil with Streptomyces sp. GanoSA1 on oil palm growth and Ganoderma disease development. (October 2020) - Shariffah-Muzaimah, Syed Aripin; Idris, Abu Seman; Nur-Rashyeda, Ramli; Naidu, Yuvarani; ZainolHilmi, Nur H.; Norman, Kamarudin
Abstract: Basal stem rot (BSR) or Ganoderma disease is a huge problem for palm oil producers worldwide because it severely damages infected palms and significantly affects yield. Previous studies have indicated that actinomycetes have potential applications as biological control agents against a range of phytopathogens. The aim of this study was to assess whether an application of actinomycetes could potentially reduce the disease incidence in oil palm plantations. In total, 129 Streptomyces -like isolates were purified from oil palm rhizospheric soils and tested against Ganoderma boninense PER71 in vitro . Of these, isolate GanoSA1 exhibited the strongest mycelial inhibition of G. boninense PER71. Molecular identification using 16S rRNA gene sequence analysis indicated that GanoSA1 had a high level of sequence similarity to Streptomyces nigrogriseolus . GanoSA1 was able to tolerate a wide range of temperatures, pH levels, and NaCl concentrations, and tests for the production of hydrolytic enzymes, siderophores and phosphate solubilization were positive. In tests for tolerance to commercial herbicides, GanoSA1 exhibited tolerance to field application levels of glyphosate isopropylamine at all concentrations tested (i.e., 1.0%, 0.5%, and 0.25%). Seedlings grown in soil mixed with a GanoSA1 vermiculite powder formulation (10 8 colony forming units/g) showed a higher vegetative growth index and lower disease incidence (48.89% versus 91.11%), decreased severity of foliar symptoms, and lower mortality six months after treatment than untreated control seedlings. GanoSA1 enhanced the growth of oil palm seedlings and reduced the incidence of BSR, suggesting that GanoSA1 may have a potential use as a biological control agent. Highlights: Streptomyces nigrogriseolus GanoSA1 was isolated from the rhizospheric area of oil palm plantation. Streptomyces nigrogriseolus GanoSA1 shows efficacy on Ganoderma disease incidence in oil palm seedlings in nursery trial. Soil mixing with vermiculite powder containing Streptomyces nigrogriseolus GanoSA1 enhance oil palm growth. Streptomyces nigrogriseolus GanoSA1 could be considered as potential biocontrol for controlling Ganoderma boninense .